2021
DOI: 10.1128/msystems.00943-21
|View full text |Cite
|
Sign up to set email alerts
|

Different Regulatory Modes of Synechocystis sp. PCC 6803 in Response to Photosynthesis Inhibitory Conditions

Abstract: Cyanobacteria are a compelling biochemical production platform for their ability to propagate using light and atmospheric CO 2 via photosynthesis. However, the engineering of strains is hampered by limited understanding of photosynthesis under diverse environmental conditions such as high-light and low-temperature stresses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…In our analysis we included 691 and 957 intrinsic termination sites predicted by TERMITe in E. coli based on the data described in this study and Choe et al (17), respectively; 635, 1165, 984 and 1214 sites of B. subtilis based on data from Chhabra et al (15), Mandell et al (7), Dar et al (14) and Mondal et al (8), respectively; 796 terminators from E. faecalis (14); 862 terminators from L. monocytogenes (14); 206 terminators from Z. mobilis (24); 165 terminators from Synechocystis sp . (16); 629 terminators from S. coelicolor (20), 573 terminators from S. venezuelae (20); 520 terminators from S. tsukubensiis (20); 737 terminators from S. griseus (22); 495 terminators from S. lividans (20); 435 terminators from S. clavuligerus (21); 707 terminators from S. avermitilis (20) (Supplementary Figure 3A). All of the above-listed terminators have been identified using TERMITe as described in the Methods section.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our analysis we included 691 and 957 intrinsic termination sites predicted by TERMITe in E. coli based on the data described in this study and Choe et al (17), respectively; 635, 1165, 984 and 1214 sites of B. subtilis based on data from Chhabra et al (15), Mandell et al (7), Dar et al (14) and Mondal et al (8), respectively; 796 terminators from E. faecalis (14); 862 terminators from L. monocytogenes (14); 206 terminators from Z. mobilis (24); 165 terminators from Synechocystis sp . (16); 629 terminators from S. coelicolor (20), 573 terminators from S. venezuelae (20); 520 terminators from S. tsukubensiis (20); 737 terminators from S. griseus (22); 495 terminators from S. lividans (20); 435 terminators from S. clavuligerus (21); 707 terminators from S. avermitilis (20) (Supplementary Figure 3A). All of the above-listed terminators have been identified using TERMITe as described in the Methods section.…”
Section: Resultsmentioning
confidence: 99%
“…follow a bimodal distribution. It was previously suggested that such distribution is related to the evolution of two distinct mechanisms of transcription termination (Rho-dependent and Rho-independent/intrinsic) (16, 21, 22). Thus, the observed bimodality might suggest that the Rho-dependent mechanism might be utilized more often in the GC-rich Streptomyces genus than in other bacteria, having less GC-rich genomes, which is in agreement with the observed lowest fraction of intrinsic terminators among all identified 3’ RNA termini.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both temperature and UVR stress can lead to increased production of ROS, potentially generating oxidative stress. The antioxidant enzyme SOD responds rapidly by catalyzing the conversion of superoxide radicals into H 2 O 2 that is then converted to H 2 O by CAT ( Rastogi et al, 2014 ; Cho et al, 2021 ). In this study, cells grown at elevated temperature showed higher SOD and CAT activity than that at 25°C, and the subsequent exposure with UVR further stimulated the activity of both antioxidases, indicating their protective role in mitigating harmful effects of oxidative stress caused by UVR.…”
Section: Discussionmentioning
confidence: 99%
“…We collected transcription termination sites (TTSs) defined by published genome-wide studies [4,[27][28][29][30][31][32][33][34][35] (Table S1). Naively training models on experimentally verified TTS presented several challenges.…”
Section: Data Collection Augmentation and Context-aware Model Trainingmentioning
confidence: 99%